Role of clinical tutors in volunteering work camps. (April 2014) - Alloni, Rossana; D'Elia, Annunziata; Navajas, Francisca; De Gara, Laura
Summary Background The Università Campus Bio‐Medico (Italy) promotes a summer volunteering work camp (Workcamp Perù) as a social activity for medical and non‐medical students. Some junior doctors participate as 'clinical tutors', together with tutors from other professions; all clinical tutors have some teaching experience in our teaching hospital. Context The campsite is located in the South of Peru in the Cañete Valley, an area characterised by extreme poverty and a severe lack of infrastructure. During the five Workcamp Perù trips that have been organised so far, health science students have carried out many activities for disease prevention and health education, and bio‐medical engineering students have organised sessions on the safety of electrical installations, for accident prevention. Innovation and implications We observed that in this setting tutorial activity is fundamental, because it not only offers students an opportunity to learn but also encourages them to react in a more personal and reflective manner to various stressful situations, which often occur in the work camp. The professional competence of the tutor plays an important role before the work camp, in defining the learning objectives for the students and involving them in training sessions held prior to the work camp. Also, during the camp, tutors work with students and also direct the daily briefing and debriefing sessions that are the most important learning activity. For medical tutors involved in the work camp the volunteering experience is a challenge for developing their specific professional and teaching skills, but it also provides an enriching experience in both professional and personal terms. We consider these work camps to be a useful experience in the training of our clinical tutors.